Analisis Faktor-Faktor yang Mempengaruhi Urban Heat Island di Kota Bandarlampung - Mia Ermawati; Andi Syahputra; Titin Mutmainah (REKA RUANG, 2022)
Urban Heat Islands (UHI) has occurred in several major urban areas worldwide, also in several urban areas in Indonesia. This occurrence has caused many negative impacts, such as inconvenience in people’s daily activity, excessive use of energy, and health problems. There are several factors that may contribute on the formation of UHI, which are Green House Gas (GHG) emission and land use change. Understanding the factors that significantly contribute on the formation of UHI is important to minimize its effect. Using a case study in Bandarlampung, a middle-sized city in south part of Sumatera, this research is conducted to investigate the effect of vegetation and building on the formation of UHI. This research utilized NDVI, NDBI, and LST method to identify vegetation and building density, and surface temperature. Analysis result shows that the highest UHI Value in Bandarlampung exists in the UHI III category, with the value of UHI in 2016 was 0,1 degrees higher than the one in 2020. This research may demonstrate that the vegetation and building density contribute significantly in the formation of UHI in the case study area.